2018
DOI: 10.1155/2018/6397340
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Health Education on Knowledge and Behaviors toward Infectious Diseases among Students in Gansu Province, China

Abstract: Objectives Infectious disease knowledge and behaviors are key elements that ensure student health and safety. This study explores the impact of health education on student knowledge and behaviors toward infectious diseases and determines the factors affecting infectious diseases knowledge and behaviors among students in Gansu, China. Methods A cross-sectional study and three sampling methods were used in two counties, 12 schools, and 32 classes in Gansu, China, from 2012 to 2013. Collected data included the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
63
2
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(86 citation statements)
references
References 14 publications
13
63
2
8
Order By: Relevance
“…We found also that respondents who had secondary or high education had higher likelihood of having correct knowledge about TB transmission. Our results are consistent with prior literature [46] Eventually, improved levels of education in the community can improve cognitive level and increase the general knowledge about infection control including TB and the general health of the people [51]. Furthermore, as with previous literature [26] [35], the current study found that respondents from the richest households had high chances of having correct knowledge about TB transmission.…”
Section: Discussionsupporting
confidence: 92%
“…We found also that respondents who had secondary or high education had higher likelihood of having correct knowledge about TB transmission. Our results are consistent with prior literature [46] Eventually, improved levels of education in the community can improve cognitive level and increase the general knowledge about infection control including TB and the general health of the people [51]. Furthermore, as with previous literature [26] [35], the current study found that respondents from the richest households had high chances of having correct knowledge about TB transmission.…”
Section: Discussionsupporting
confidence: 92%
“…These results correlated with a study by Suraweera, Galgamuwa, Iddawela, & Wickramasinghe (2015). However, several other studies showed that the habits of biting fingers and sucking fingers could be determinant factors of pinworm infections (Anuar, Jalilah, Norhayati, Azlin, & Fatmah, 2016;Wang et al, 2018). A study conducted by Merad, Merbouh, Benallal, Belfodel, & Adjmi-Hamoudi (2018) showed that the habits of biting and sucking fingers are a major risk factor for pinworm infection, which indicates that the transmission process occurs orally from hand to mouth.…”
Section: Discussionsupporting
confidence: 82%
“…Other studies showed that the prevalence of pinworm infections in children who have a habit of scratching their buttocks area is higher than in those that do not. Pinworm eggs in the perianal area can move to the hands when a child scratches their buttocks area, thereby increasing the risk of pinworm infections (Dahal & Maharjan, 2015;Wang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang ve ark. 4 sağlık eğitimi ile farklı ülkelerde hastalıklara karşı davranışlar arasındaki ilişkiyi incelemiş ve sağlık eğitimi alan nüfusun hastalıklara karşı önemli ölçüde önleyici davranışlara sahip olduğu sonucuna ulaşmıştır. King ve ark.…”
Section: Introductionunclassified